Integrating Language Skills into Journalism Practice for Higher Education: Perspectives from Students and Lecturers - Fujita Yusandra, Titiek; Ermanto; WS, Hasanuddin (Digital Technologies Research and Applications, 2025)
Integrating language skills into journalism education is crucial for preparing students to meet professional demands in the media industry. The purpose of this study is to explore the integration of language skills into journalism practice based on the perspectives of students and lecturers directly involved in journalism activities. This study stems from the gap between the practical skills required by students and the available learning mate‑rials, which often leaves graduates unprepared to meet the demands of the media industry. This study employs a mixed‑method approach, distributing questionnaires to 64 students from three universities: Universitas Bung Hatta, Universitas PGRI West Sumatra, and Universitas Muhammadiyah West Sumatra. Semi‑structured interviews were also conducted with three lecturers teaching journalism practice courses at each university. The research findings indicate that the most needed skills include news writing, headline creation, script reading for audiovisual production, and news video editing. The four basic language skills, listening, speaking, reading, and writing, are considered essential for integration into journalism practice modules. These findings suggest that developing contextual industry‑oriented journalism learning materials can enhance students' competencies comprehensively, fostering graduates who are adaptive, competent, and ethical in producing credible journalistic work. The study contributes insights for designing journalism education that aligns with language learning integration and professional newsroom expectations.